2010
DOI: 10.1007/s11033-010-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of catalytically active cross-species heterodimers of thymidylate synthase from Plasmodium falciparum and Plasmodium vivax

Abstract: Thymidylate synthase (TS) of Plasmodium dihydrofolate reductase-thymidylate synthase (DHFR-TS) functions as a homodimeric enzyme with two active sites located near the subunit interface. The dimerization is essential for catalysis, since the active site of each subunit contains amino acid residues contributed from the other TS domain. In P. falciparum DHFR-TS, it has been shown that the active sites require Cys-490 from one domain and Arg-470 donated from the other domain. Mutants of these two series can compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…In addition, PbPf S108N transgenic parasites grew the same as PbGFP parasites. This result demonstrated that the DHFR-TS function is conserved between the two Plasmodium species, in agreement with other cross-species comparisons in the same genus [22]. Furthermore, the pyrimethamine resistance mutation had no negative effect on the function of the enzyme, in agreement with earlier studies [21,23].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, PbPf S108N transgenic parasites grew the same as PbGFP parasites. This result demonstrated that the DHFR-TS function is conserved between the two Plasmodium species, in agreement with other cross-species comparisons in the same genus [22]. Furthermore, the pyrimethamine resistance mutation had no negative effect on the function of the enzyme, in agreement with earlier studies [21,23].…”
Section: Discussionsupporting
confidence: 91%
“…The fact that it is possible to replace the endogenous Plasmodium dhfr-ts with a homologue from a different species suggests that dhfr-ts function is conserved among species of this genus. This is in agreement with biochemical evidence that cross-species heterodimers of Plasmodium DHFR-TS are fully functional [34]. While the expression of double mutant Pv DHFR-TS SP21 was not deleterious and can support the growth of the transgenic P. berghei parasites, attempts to obtain P. falciparum stably expressing double mutant Pv DHFR-TS SP21 were not successful (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Among the 11 drug resistance genes with positive selection signals, six genes are involved in chloroquine resistance, and three other genes are associated with multidrug resistance. The dihydrofolate reductase gene which confer resistance to pyrimethamine ( dhfr - ts , PVX_089950) was also found [48]. A recent study in Peru found haplotypes in drug-resistance genes including dhfr and mdr , suggesting that resistance mutations have arisen independently and might be directly linked to the widespread use of chloroquine, artemisinin and primaquine [49].…”
Section: Discussionmentioning
confidence: 99%